Role of supportive periodontal management in patient with metastatic cancer - Kevin Chee Pheng Neo; Nurul Syahirah Mohamad; Avita Rath; Melissa Li Zheng Wong; Myint Wai; Bennete Fernandes (Dental Journal, 2022)
Background: Treatment of head and neck cancers may cause sequelae affecting patients’ quality of life during and after treatment. As a result, periodontal management of a patient with parotid gland adenoid cystic carcinoma, particularly in advanced stage 4, can be challenging for dental practitioners, especially if the patient is on active oral molecular therapy and undergoing long-term radiotherapy and chemotherapy. Purpose: This report was intended to describe the conservative non-surgical management of tooth 27 with poor prognosis owing to grade II mobility in a patient on active Lenvatinib therapy – where the extraction was not advisable to lessen the risk of osteonecrosis. Case: A 52-year-old female patient was referred by an oncologist to our dental clinic for noncarious toothache. Five years ago, the patient was diagnosed with adenoid cystic carcinoma (ACC) and had a treatment history of radiotherapy, chemotherapy and surgical removal of the left parotid gland to manage the malignancy. Oral examination revealed characteristic findings of periodontitis. Case Management: Ultrasonic scaling, antimicrobial mouth rinses and reinforcement in oral hygiene instructions manage the tooth 27 conservatively. Conclusion: A cautious approach by the dental surgeon, together with the multidisciplinary team caring for cancer patients, is fundamental and helps with the palliative periodontal management of this patient to enhance oral health-related quality of life. With a lack of reports on conservative periodontal therapy in ACC patients, this report highlights the combination of smoking cessation, reinforcement of oral hygiene instructions and conservative periodontal treatment.